2007
DOI: 10.4081/ijas.2007.1s.823
|View full text |Cite
|
Sign up to set email alerts
|

Response of captive seabass and seabream as behavioural indicator in aquaculture

Abstract: Welfare of cultivate fish at high-density represents an important concern for modern aquaculture. The behaviour of European seabass (Dicentrarchus labrax) and seabream (Sparus aurata) reared in cages was studied in a fish farm of northern Sardinia (Italy) in autumn 2006 to test whether captive condition had an effect on the movement patterns of these two species.Video images recorded before, during and after the manual feeding distribution allowed us to collect data on different behaviours of captive fish. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…This fact agrees with the assumption that the occurrence of fin damage and erosion is substantially greater under reared conditions than in the natural environment, possibly due to the high densities, feeds provided and aquaculture operations (Mork et al, 1989). Sara`et al (2007) demonstrated that the most frequent movements of farmed seabream inside cages were, apart from horizontal and vertical movements, collisions between fishes. According to this, it was evidenced that the most exposed finspectoral, caudal and dorsalfrom farmed seabream resulted in the highest erosion.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This fact agrees with the assumption that the occurrence of fin damage and erosion is substantially greater under reared conditions than in the natural environment, possibly due to the high densities, feeds provided and aquaculture operations (Mork et al, 1989). Sara`et al (2007) demonstrated that the most frequent movements of farmed seabream inside cages were, apart from horizontal and vertical movements, collisions between fishes. According to this, it was evidenced that the most exposed finspectoral, caudal and dorsalfrom farmed seabream resulted in the highest erosion.…”
Section: Discussionsupporting
confidence: 87%
“…Sarà et al. () demonstrated that the most frequent movements of farmed seabream inside cages were, apart from horizontal and vertical movements, collisions between fishes. According to this, it was evidenced that the most exposed fins – pectoral, caudal and dorsal – from farmed seabream resulted in the highest erosion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to applications to fish ecology and monitoring, video recording techniques have also been used for commercial purposes in aquaculture and fisheries. Aquaculture studies have used such techniques to estimate abundance and biomass of bluefin tuna (Costa et al 2009;Mariani et al 2014) or behavioral changes of captive fish under different conditions (Sarà et al 2007;. Fisheries studies use video techniques to estimate the catchability of fishing gears (Dremière et al 1999;Papadopoulou et al 2015) and record the effect fish aggregating devices can have on fish community structure (Addis et al 2016) or fish behavior (Sinopoli et al 2015).…”
Section: Introductionmentioning
confidence: 99%